2022
DOI: 10.1155/2022/4514669
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Effect of Holistic Nursing in the Operating Room Based on PDCA and Evidence‐Based Nursing in the Otorhinolaryngology Operating Room: Based on a Retrospective Case‐Control Study

Abstract: Objective. Based on a retrospective case-control study, this study aims to explore the effect of holistic nursing in operating room based on PDCA (plan, do, check, and action) process and evidence-based nursing (EBN) in a ear, nose, and throat operating room. Methods. About 200 patients who underwent otorhinolaryngology surgery in our hospital from January 2019 to September 2021 were enrolled. According to the difference of nursing mode, patients were assigned into a control group and study group; holistic nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our research is still clinically significant, and further in-depth investigations will be carried out in the future. The same idea can be found in the study put forward by Bian [45]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
supporting
confidence: 71%
“…Our research is still clinically significant, and further in-depth investigations will be carried out in the future. The same idea can be found in the study put forward by Bian [45]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
supporting
confidence: 71%
“…[15][16][17] Moreover, due to the inherent operational reasons of this examination method, many patients' feelings of pain during the examination lead to many problems with their actual situation. [18][19][20][21] PDCA management mode is a new management concept proposed by a management expert in the United States, Dai Ming. It mainly includes 4 steps, namely, P (plan), D (implementation), C (inspection), and A (treatment).…”
Section: Discussionmentioning
confidence: 99%
“…[15–17] Moreover, due to the inherent operational reasons of this examination method, many patients’ feelings of pain during the examination lead to many problems with their actual situation. [18–21]…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%